The Effectiveness of The Halal Product Guarantee Law on Business Awareness in Registration of Halal Certification in Indonesia - Anzellyta, Tasya; Fittria, Anis (Walisongo Law Review (Walrev), 2022)
The issuance of the Law on Halal Product Assurance in 2014 marked a new era of halal certification in Indonesia. In the past, halal certification was voluntary, but after the JPH Law it became mandatory. The government through the Halal Product Guarantee Agency of the Ministry of Religion of the Republic of Indonesia is tasked with guaranteeing halal products in the community. The fact is that until 2022, there are still many business actors, especially those on the Small, Medium and Micro scale (MSMEs) who have not registered for halal certification. Even though the regulation has existed since 2014. Based on this, this study aims to determine the effectiveness of the Halal Product Guarantee Act on the Awareness of Business Actors in the Registration of Halal Certification in Indonesia. The research method used in this research is qualitative field research, with an empirical juridical research approach. The results of this study indicate that the Halal Product Guarantee Act has not been effective in increasing the awareness of business actors to register for halal certification and increase the availability of halal products in Indonesia. The minimum number of business actors who register for halal certification is influenced by legal awareness, namely: knowledge of legal regulations, knowledge of legal content, legal attitudes, and legal behavior. It is concluded that business actors in Indonesia have a low level of legal awareness in registering for halal certification. Many business actors do not know about the obligation of halal certification. There are also business actors who already know about halal certification, but have not yet arrived at compliance and carrying out the mandate of the Halal Product Guarantee Act. Terbitnya Undang-undang tentang Jaminan Produk Halal (UU JPH) pada tahun 2014 menandai era baru sertifikasi halal di Indonesia. Dahulu, sertifikasi halal bersifat sukarela (voluntary), akan tetapi setelah adanya UU JPH menjadi wajib (mandatory). Pemerintah melalui Badan Penyelenggara Jaminan Produk Halal (BPJPH) Kementrian Agama Republik Indonesia bertugas untuk menjamin produk halal di masyarakat. Faktanya sampai tahun 2022, masih banyak pelaku usaha terutama yang berskala Usaha Kecil, Menengah dan Mikro (UMKM) yang belum melakukan pendaftaran sertifikasi halal. Padahal regulasinya sudah ada sejak tahun 2014. Berdasarkan hal tersebut, maka penelitian ini bertujuan untuk mengetahui efektivitas Undang Undang Jaminan Produk Halal Terhadap Kesadaran Pelaku Usaha dalam Pendaftaran Sertifikasi Halal di Indonesia. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian lapangan (field research) yang bersifat kualitatif, dengan pendekatan penelitian yuridis empiris. Hasil penelitian ini menunjukan bahwa Undang-undang Jaminan Produk Halal (UU JPH) belum efektif dalam meningkatkan kesadaran pelaku usaha untuk pendaftaran sertifikasi halal dan meningkatkan ketersediaan produk halal di Indonesia. Minimnya jumlah pelaku usaha yang mendaftar sertifikasi halal ini dipengaruhi oleh kesadaran hukum, yakni: pengetahuan tentang peraturan hukum, pengetahuan isi hukum, sikap hukum, dan perilaku hukum. Disimpulkan bahwa pelaku usaha di Indonesia memiliki tingat kesadaran hukum yang masih rendah dalam mendaftar sertifikasi halal. Pelaku usaha banyak yang belum tahu tentang kewajiban sertifikasi halal. Ada juga pelaku usaha yang sudah tahu tentang sertifikasi halal, namun belum sampai pada ketaatan dan melaksanakan amanat Undang-undang Jaminan Produk Halal.